2006
DOI: 10.1007/s10615-005-0037-x
|View full text |Cite
|
Sign up to set email alerts
|

Delusional themes of penetration and loss of boundaries and their relation to early sexual trauma in psychotic disorder

Abstract: This paper explores how the psychotic experience of the penetration of destructive objects and a loss of boundaries appears in the delusions experienced by a woman who reported early sexual trauma. Through a close analysis of these psychotic experiences, this research seeks to illustrate how a psychotic personality organization, coupled with repeated early attacks on the integrity and boundaries of the self, can create a pervasive sense of being relentlessly pursued and penetrated by destructive objects. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Included for analysis was only empirical retrospective studies, published between 1992 and 2019, in which women survivors of CSA self-reported loss relating to their CSA. Of the studies for the summary analysis, the majority ( n = 13) were from the United States, one study each was found in Australia (Goldman & Bode, 2012), Canada (Mcevoy & Daniluk, 1995), New Zealand (Romans et al, 2001), Israel (Chopra, 2006), and South Africa (Ebrahim et al, 2018), and two were unspecified (Oz, 2005; Roth & Newman, 1992). Ten of the 20 studies specified the participant’s race.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Included for analysis was only empirical retrospective studies, published between 1992 and 2019, in which women survivors of CSA self-reported loss relating to their CSA. Of the studies for the summary analysis, the majority ( n = 13) were from the United States, one study each was found in Australia (Goldman & Bode, 2012), Canada (Mcevoy & Daniluk, 1995), New Zealand (Romans et al, 2001), Israel (Chopra, 2006), and South Africa (Ebrahim et al, 2018), and two were unspecified (Oz, 2005; Roth & Newman, 1992). Ten of the 20 studies specified the participant’s race.…”
Section: Resultsmentioning
confidence: 99%
“…There was a clear indication in three studies that personal boundaries were violated and/or disrespected during the CSA abuse (Chopra, 2006; Schwerdtfeger & Wampler, 2009; Thomas & Hall, 2008). Through the experience of CSA survivors feel that their personal dignity is betrayed, this may lead to survivors feeling dependent on the perpetrator, as the perpetrator allowed them to feel cared for and protected (Liem et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations